Hubungan Literasi Kesehatan terkait Gizi dan Pola Konsumsi Sayur dan Buah pada Mahasiswa Selama Masa Pandemi COVID-19 - Ratu Dien Prima Fermeza; Emyr Reisha Isaura (Universitas Airlangga, 2022)
Background: The current condition of people's food consumption still does not meet the balanced nutrition guidelines because the Indonesian population is still classified as lacking in consuming vegetables and fruit. Previous research stated that students were classified as lacking in consumption of vegetables and fruit during the pandemic. Students undergoing distance learning encourage increased use of mobile devices and health-related searches. Objective: To analyze the relationship between nutrition-related health literacy and vegetable and fruit consumption patterns in college students during the COVID-19 pandemic. Methods: This study is a cross-sectional study. The research was conducted online using a google form which was distributed through social media. The number of samples in this study was 150 people with the purposive sampling method. The instruments used are SFLQ to determine the level of health literacy related to nutrition and SQ-FFQ to measure the pattern of eating vegetables and fruits in one month. Results: The results showed that late teens (58.6%), girls (46.0%), early year students (29.7%), and students in non-health studies (26.0%) were classified as having less vegetable consumption. and fruit. Nutrition-related health literacy related to vegetables and fruit consumption during COVID-19 pandemic Conclusion: The majority of Airlangga University students during the COVID-19 pandemic had a sufficient level of consumption of vegetables and fruit and good literacy. There was a significant relationship between gender (p=0.007) and health literacy related to nutrition (p=0.002) with consumption patterns of vegetables and fruit. Keywords: health literacy, vegetables and fruit, college students